Rotor Speed Analysis of SMC-based IFOC for Low-Speed Induction Motor Control - Aditya, Angga Wahyu; Ihsan, Ihsan; Husaini, Fachri; Ramadhanu, Faisal Faiiz (ELKHA : Jurnal Teknik Elektro, 2023)
The control of electric motors, particularly three-phase induction motors, has developed rapidly due to their application in industry. Indirect Field Oriented Control (IFOC) is one of the most widely used control systems due to its ease of application. IFOC controls a three-phase induction motor in the same way as a DC motor. However, IFOC requires a Sliding Mode Control (SMC) controller with Lyapunov stability theory to ensure robustness and stability. In exceptional conditions, such as low-speed settings, the SMC-based IFOC requires unique sets to operate with a steady-state error (Ess) at a speed response of less than 2%. Other parameters to be considered are rise time and electromagnetic torque response at low speeds. The addition of the boundary layer of the hyperbolic tangent function to a first-order SMC can increase induction motor (IM) control up to 175 rpm with a value of Ess = 1.96% compared to the saturation and signum functions, which are only capable of a reference speed of 300 rpm in no-load conditions with a value of Ess = 2% for the saturation function and 1.94% for the signum function. SMC with the hyperbolic tangent function boundary layer performs best under load conditions. The rising time value does not significantly differ under no-load or torque-load conditions between the SMC with the saturation, hyperbolic tangent function boundary layers and without the boundary layer. Adding a boundary layer with the hyperbolic tangent function can reduce ripple significantly compared to the saturation function under no-load or load conditions.